What is qualitative interviewing? - Edwards, Rosalind; Holland, Janet (New Delhi Bloomsbury, 2018)
What is Qualitative Interviewing? is an accessible and comprehensive 'what is' and 'how to' methods book. It is distinctive in emphasising the importance of good practice in understanding and undertaking qualitative interviews within the framework of a clear philosophical position. Rosalind Edwards and Janet Holland provide clear and succinct explanations of a range of philosophies and theories of how to know about the social world, and a thorough discussion of how to go about researching it using interviews.